2018
DOI: 10.1016/j.canlet.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Tannins from Syzygium guineense suppress Wnt signaling and proliferation of Wnt-dependent tumors through a direct effect on secreted Wnts

Abstract: Triple-negative breast cancer (TNBC) and colon cancer (CC) are two stigmatic examples of poorly treatable tumors, whose progression critically depends upon hyperactivation of the Wnt signaling. Development of specific anti-Wnt inhibitors is required to develop drugs against these and other Wnt-dependent cancers. Natural products, especially plants, have been used for the treatment of various diseases from ancient times. We examined extracts from several indigenous Cameroonian herbs and tested their effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 60 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…This result was in agreement with a previous study used CTs from black beans that showed anti-proliferation activity against several cancer cell types (Bawadi et al, 2005). Tannin extracts might also interfere with oncogenic pathways such as Wnt as a recent study showed the inhibitory effect of tannins on the Wnt signaling pathway and cancer cell proliferation (Koval et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This result was in agreement with a previous study used CTs from black beans that showed anti-proliferation activity against several cancer cell types (Bawadi et al, 2005). Tannin extracts might also interfere with oncogenic pathways such as Wnt as a recent study showed the inhibitory effect of tannins on the Wnt signaling pathway and cancer cell proliferation (Koval et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, S. guineense extract could suppress Wnt3a-related β-catenin stabilization and transcript response. [82] The ethanol extract of Cyperus rotundus L. (EECR) inhibited the proliferation of MDA-MB-231 and MDA-MB-468 cells in a dose-dependent manner, and it blocked the cell cycle of G0/G1 phase. EECR could induce apoptosis by promoting the expression of Bax and inhibiting the expression of Bcl-2.…”
Section: Natural Extracts With Anti-tnbc Activitiesmentioning
confidence: 99%
“…XAV939 and clofazimine have been identified as Wnt inhibitors and promising anti-TNBC drugs, but neither of them have yet been used in advanced clinical trials [80,81]. Fortunately, tannins, isolated from Syzygium guineense, directly inactivates the stabilization and transcription of Wnt3a-induced β-catenin expression, which may be pursued for novel therapies [82]. As the most potent anti-cancer carotenoids in saffron, crocin exhibits a more potent anti-metastatic ability on TNBC through downregulating FZD7 mRNA expression and upregulating Ecadherin expression in the Wnt/β-catenin pathway [83].…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%